Representativeness of the PDOPPS cohort compared to the Australian PD population. Issue 4 (July 2022) - Ethier, Isabelle; Boudville, Neil; McDonald, Stephen; Brown, Fiona; Kerr, Peter G; Walker, Rowan; Holt, Stephen Geoffroy; Badve, Sunil V; Cho, Yeoungjee; Hawley, Carmel; Robison, Laura; Reidlinger, Donna; et al.
Background: The Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS) is an international, prospective study following persons treated by peritoneal dialysis (PD) to identify modifiable practices associated with improvements in PD technique and person survival. The aim of this study was to assess the representativeness of the Australian cohort included in PDOPPS compared to the complete Australian PD population, as reported to the Australia and New Zealand Dialysis and Transplant (ANZDATA) Registry. Methods: Adults with at least one PD treatment reported to ANZDATA Registry during the census period of PDOPPS Phase I (November 2014 to April 2018) were compared to the Australian PDOPPS cohort. The primary outcomes were the representativeness of centres and persons. Secondary outcomes explored the association of person characteristics with consent to study participation. Results: After data linkage, 511 PDOPPS participants were compared to 5616 Australians treated with PD. Within centres eligible for PDOPPS, selected centres were similar to other Australian centres. The PDOPPS participants' cohort tended to include older persons, more males, a higher proportion of Caucasians and more persons with higher socioeconomic advantage compared to the Australian PD population. Differences in distribution across sex and ethnicities between the PDOPPS cohort and the overall PD population were in part due to the selection and consent processes, during which females and non-Caucasians were more likely to not consent to PDOPPS participation. Conclusion: Sampling methods used in PDOPPS allowed for good national representativeness of the included centres. However, representativeness of the unweighted PDOPPS sample was suboptimal in regard to some participant characteristics.